MOTIVATIONAL READINESS OF FRESHMEN TO STUDY AT MEDICAL HEIs - Shepitko, V.I.; Єрошенко, Г.А.; Bilash, S.M.; Lisachenko, O.D.; Вільхова, О.В.; Климач, Т.М. (World of Medicine and Biology, 2015)
In the article the brought results of psychological research, in relation to motivation to the studies, that was conducted among the students of the first course medical, stomatological departments of the “Ukrainian medical stomatological academy”. It was established that leading reasons of educational activity of students are acquisitions of thorough knowledge, to become a highly skilled specialist, to get a diploma, to study successfully, to pass exams “good” and “excellent”, to provide success in the future professional activity. The least meaningful reasons, according to research, were the following: to be constantly ready to the next class, not to introduce the subjects of the curriculum, to meet the tutor’s requirements, to be an example for peers, to avoid conviction and punishments for poor studies.